SrCl2 Derived Perovskite Facilitating a High Efficiency of 16% in Hole‐Conductor‐Free Fully Printable Mesoscopic Perovskite Solar Cells - Zhang, Hua; Wang, Huan; Williams, Spencer T.; Xiong, Dehua; Zhang, Wenjun; Chueh, Chu‐Chen; Chen, Wei; Jen, Alex K.‐Y. (Advanced materials (Weinheim), 2017)
Despite the breakthrough of over 22% power conversion efficiency demonstrated in organic–inorganic hybrid perovskite solar cells (PVSCs), critical concerns pertaining to the instability and toxicity still remain that may potentially hinder their commercialization. In this study, a new chemical approach using environmentally friendly strontium chloride (SrCl2) as a precursor for perovskite preparation is demonstrated to result in enhanced device performance and stability of the derived hole‐conductor‐free printable mesoscopic PVSCs. The CH3NH3PbI3 perovskite is chemically modified by introducing SrCl2 in the precursor solution. The results from structural, elemental, and morphological analyses show that the incorporation of SrCl2 affords the formation of CH3NH3PbI3(SrCl2)x perovskites endowed with lower defect concentration and better pore filling in the derived mesoscopic PVSCs. The optimized compositional CH3NH3PbI3(SrCl2)0.1 perovskite can substantially enhance the photovoltaic performance of the derived hole‐conductor‐free device to 15.9%, outperforming the value (13.0%) of the pristine CH3NH3PbI3 device. More importantly, the stability of the device in ambient air under illumination is also improved. A new compositional perovskite, CH3NH3PbI3(SrCl2)0.1 with more compact morphology and lower defect concentration is presented. Consequently, a power conversion efficiency of 15.9% with enhanced stability is achieved by employing the structure of hole‐conductor‐free fully printable mesoscopic perovskite solar cell.